Mel Marshall on evolving coaching - Marshall, M. (Supporting champions, 2020)
This week`s guest is Mel Marshall. As a swimmer Mel made five Olympic finals at two Olympic games` and she is one of the most decorated swimmers for England at the Commonwealth Games. You`re likely to know Mel as much for her reputation as an elite swimmer as the coach of perhaps the most dominant swimmer on the planet at the moment - the imperious Adam Peaty.